Availability of Reformative Education Programmes for Prisoners in North West Nigeria - Dr. Suleiman Ismaila (University of Management and Technology, 2020)
The study investigated the availability of reformative education programs for prisoners in northwest Nigeria. A descriptive survey was the adopted research design. The target population comprised the stakeholders (prison inmates, prison officials, lawyers, and human rights activists) from four states (Kaduna, Katsina, Jigawa, and Kano) northwest Nigeria. A total of 13 prisons, 1338 respondents (1068 inmates; 200 prison officials; 50 lawyers; and 20 human rights activists) were selected using multi-stage sampling. Four questionnaires designed by the researcher were used for data collection dedicating one questionnaire to each of the stakeholders. The validity of the instruments was ascertained using content and construct validity. The calculated value of Cronbach Alpha was 0.87. The data collected from the study were analyzed using descriptive statistics. The hypotheses were tested using chi-square. The findings of the study revealed that out of the five indicators of prisoners' reformative education, only one was available, that is, religious education. However, the other four, facilities, personnel, and reading materials; educational continuity and motivation; remedial and adult education, and vocational education were unavailable. The study recommended that prisons should be equipped with modern facilities for valuable reformative education. There should be training and retraining of prison personnel, and a well-stocked library with current and updated materials containing textbooks, periodicals and computers be provided in all prisons for the use of both inmates and prison officials, among others.